2002
DOI: 10.1051/radiopro/2002036
|View full text |Cite
|
Sign up to set email alerts
|

Is it relevant to take into account the multipollution context in freshwater radioecology ?

Abstract: Abstract. Should realism of radioecological evaluations be enhanced while taking into account the deleterious influence of stable pollutants on aquatic organisms which can be physiologically stressed, and therefore can modify their response to radionuclide bioaccumulation? Transfer experiments in a multipollution context involved metals {Cd, Zn), organic pollutants (PCBs, PAHs, oestrogenomimetics) and radionuclides (radioactive isotopes of Co, Cs, and Ag). The chosen biological models were a freshwater bivalve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2004
2004

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…The relevance of considering the influence of multipollution in radioecological assessment models has been proved various examples. Among others, laboratory transfer experiments in a multipollution context have shown that chronic metallic waterborne exposures (1-4 µg l −1 Cd and/or 170-250 µg l −1 Zn) led to a decrease in radionuclide bioaccumulation with respect to the reference group (uptakes of Ag and Cs in fish reduced by 60% and 30%, respectively; uptake of Co in bivalves reduced by 50%, on average); whereas no effect was found with other radionuclide/organism pairs (Co for fish, Cs and Ag for bivalves) [28]. Prior exposure to organic micropollutants enhanced 57 Co and 134 Cs uptake kinetic parameters from water and retention time in fish; the radionuclide contamination levels of exposed groups were always higher than those obtained from the reference groups (+10% to +60% as a function of the organic micropollutant) [29].…”
Section: Introductionmentioning
confidence: 89%
“…The relevance of considering the influence of multipollution in radioecological assessment models has been proved various examples. Among others, laboratory transfer experiments in a multipollution context have shown that chronic metallic waterborne exposures (1-4 µg l −1 Cd and/or 170-250 µg l −1 Zn) led to a decrease in radionuclide bioaccumulation with respect to the reference group (uptakes of Ag and Cs in fish reduced by 60% and 30%, respectively; uptake of Co in bivalves reduced by 50%, on average); whereas no effect was found with other radionuclide/organism pairs (Co for fish, Cs and Ag for bivalves) [28]. Prior exposure to organic micropollutants enhanced 57 Co and 134 Cs uptake kinetic parameters from water and retention time in fish; the radionuclide contamination levels of exposed groups were always higher than those obtained from the reference groups (+10% to +60% as a function of the organic micropollutant) [29].…”
Section: Introductionmentioning
confidence: 89%